Futures Trading and Market Votality in Indian Equity Market: A Study of CNX IT Index - T. Mallikarjunappa; Afsal E. M. (Asian Academy of Management Journal of Accounting and Finance, 2007)
Research on the impact of the introduction of derivatives on the market volatility has reported mixed evidences. In this paper, we study the volatility implications of the introduction of derivatives on the stock market in India using S&P CNX IT index. To account for the heteroscedasticity in the time series, GARCH model is used. We find clustering and persistence of volatility in different degrees before and after derivatives and the listing in futures has increased the market volatility. The sensitivity of the index return to domestic and global return remains same even after the introduction of futures trading. Further, the nature of the volatility has altered during the post-derivatives period with prices highly dependent on recent innovations which is a sign of improved market efficiency. Besides, volatility clustering occurs at a faster pace in the post-derivatives period. We conclude that listing of derivatives has helped price discovery process.